The difference between porcelain and composite resin shear bond strength in the administration of 4% and 19.81% silane - Ira Widjiastuti; Dwina Rahmawati Junaedi; Ruslan Effendy (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Damage to porcelain restorations such as fractures requires a repair that can be performed either directly or indirectly. Direct repair involves directly performing restoration of fractured porcelain with a composite resin application. This technique has more advantages than indirect repair because it requires no laboratory work and can be completed during a single visit. Silane, on the other hand, has been widely used and is reported to increase porcelain and composite resin attachments during the direct repair process. Purpose: This study aimed to determine the differences in shear bond strength between porcelain and composite resin during the administering of 4% and 19.81% silane. Methods: 27 porcelain samples were divided into three groups, namely: Group A - 4% silane, Group B - 19.81% silane and Group C - no silane, prior to the application of composite resin. Each sample was tested for shear bond strength by means of Autograph and fracture analysis performed through stereomicroscope and scanning electron microscope tests. Data analysis was subsequently performed using an ANOVA test. Results: There was a significant difference between the three groups with p=0.000 (p<0.005). The lowest bond strength was found in the group without silane, while the highest was in the group with 4% silane (p<0.005). Conclusion: The use of 4% silane can produce the highest shear bond strength of porcelain and resin composite.